2015
DOI: 10.5489/cuaj.2485
|View full text |Cite
|
Sign up to set email alerts
|

Extended pelvic lymph node dissection at the time of robot-assisted radical prostatectomy: impact of surgical volume on efficacy and complications in a single-surgeon series.

Abstract: Introduction:We assessed the impact of surgical volume on perioperative outcomes and complications of robotic extended pelvic lymph node dissection (ePLND). 16 [range: 8-42] in Groups 1 to 4, respectively, p = 0.001). Tumour lymph node involvement was 12% in Groups 1 and 2, 7% in Group 3 and 9% in Group 4 (p = 0.075). Overall, 115 complications were reported in 98/233 patients (42%), with a significant decrease after 175 cases (p = 0.028). In Group 4, 3 patients reported an ePLND-related bleeding requiring o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…There are no studies evaluating learning curves for lymph node dissection in ORP and only two studies evaluating learning curves for RARP. Both studies showed an increase in the number of removed lymph nodes depending on the number of RARP cases [20,21]. Comparing RARP and ORP, our data showed the same effect as for the PSM rate.…”
Section: Discussionsupporting
confidence: 69%
“…There are no studies evaluating learning curves for lymph node dissection in ORP and only two studies evaluating learning curves for RARP. Both studies showed an increase in the number of removed lymph nodes depending on the number of RARP cases [20,21]. Comparing RARP and ORP, our data showed the same effect as for the PSM rate.…”
Section: Discussionsupporting
confidence: 69%
“…ePLND extends surgery time by an average of 90 min, which increases blood loss and the risk of ischemic complications [28,33]. It can also cause obturator nerve injury, life-threatening bleeding due to iliac vessels laceration, ureteral injury, deep venous thrombosis, pulmonary embolism, and lymphocele [34,35]. The latest reports indicate the need to change the cut-off value for performing ePLND at RP from 5% to 7%, resulting from the nomogram [17].…”
Section: Discussionmentioning
confidence: 99%
“…The urological community should be sensitized about the staging impact of PLND [16][17][18][19] and possible elimination of micrometastases, 17,[20][21][22] especially during RARP. 23 On the other hand, it is also important to notice that a non-negligible percentage was exposed to the potential harm of PLND 9,24,25 when it was not recommended. Followup studies are needed in more recently treated patients.…”
Section: Resultsmentioning
confidence: 99%